FINANCIAL PERFORMANCE IMPACTS OF CORPORATE ENTREPRENEURSHIP - Bertha Silvia Sutejo (Journal of Management and Business, 2016)
This paper examine about the effect of four sub-dimensions of corporate entrepreneurship (CE) on firms’ financial performance in Indonesia. The four sub-dimensions are innovativeness, risk-taking, pro-activeness, and competitive aggressiveness. This study will use primary data by the way spread some questioner in the company. To test the financial performance effects of CE, the scale for the dimensions of CE and financial performance have been adopted from the existing literature. A series of reliability and validity tests are conducted for the measurement of the scales. Validity and reliability test and multiple regression analysis have been conducted to test the hypotheses. The results of this research will provide guidelines to help investors, managers, and also academicians to comprehend the importance of CE well on the way to create financially successful firm performance and sustain it in markets.